How to cheat at managing Windows small business server 2003 - Snedaker, Susan (Rockland, MA : Syngress, 2004)
How to Cheat at Managing Windows Small Business Server 2003 deals only with the vital, and will be a huge relief to the hundreds of thousands of managers who probably never imagined they would be managing the operating system equivalent of the Space Shuttle. * The "80/20" Rule applied to managing a Windows Small Business Server 2003 network. Concise coverage, with ready-to-use solutions, of the most commonly encountered W2K3 Server tasks and problems. * Written for the non-MCSE, with little technical training, who is responsible for running a small to medium sized network. * Microsoft has announced it will no longer support Windows NT 4 products, effective Dec. 31, 2004. Millions of small businesses that did not upgrade to Windows Server 2000 will choose to upgrade directly to Windows Server 2003, and this will be a timely book.
Essentials of Windows Small Business Server 2003 -- Understanding and designing your network -- Installing Small Business Server 2003 -- Security -- Disk management -- Managing file storage -- Managing users and groups -- Permissions, shares and group policy -- Managing client computers -- Installing and managing printers -- Disaster planning, backing up, and restoring data -- Using Exchange server and Outlook 2003 -- Managing remote connectivity -- Using Sharepoint services -- Monitoring, tuning, and troubleshooting -- Premium edition features.
Keywords: Microsoft Small business server; Client/server computing; Electronic books